Analisis Semantik pada Kata “Afnān”: Kajian Mikro Linguistik Arab terhadap Surah al-Rahman Ayat 48 - Malia Fransisca (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2023)
Surah al-Rahman is one of the surahs in the Qur'an which has its own uniqueness, namely that there is 1 verse that is repeated up to 31 times, namely the verse that reads "fabi'ayyi alaa'i robkumuma tukadzdziban". It turns out that not only this verse, the researcher will also describe other uniqueness in this paper related to the word "afnān" which in translation means trees and fruits. Referring to the meaning of the dictionary, it is irrelevant, so the researcher uses a library research approach, in this case interpretation. This writing method uses qualitative methods. This study was analyzed using micro-study of Arabic linguistics (language), namely semantics. The result of this paper is that the word "afnān" contained in Surat al-Rahman verse 48 literally means branch, color, art. Meanwhile, Tafsir Ibn Kathir and al-Wajiz explained that the meaning of the word "afnān" is the colorful fruits or several branches that have very many fruits. Meanwhile, Tafsir Jalalain explains that the meaning of the word "afnān" is raindrops or the ruins of a house. So, from these two explanations we can conclude that there are differences in the meaning of the word "afnān" in terms of quality and quantity.